Implication Of Interrogation Conversions Against Traffic Breakers: A Forensic Linguistic Study - Harist Satria; Muhammad Darwis; Firman Saleh; Kamsinah Kamsinah (La Ogi : English Language Journal, 2022)
This study describes linguistic phenomena and forms of conversational implicatures using forensic linguistic studies. The purpose of this study is to reveal the implicature analysis of juvenile traffic violations during the interrogation process and to reveal speech acts and speech events in interrogation language against juvenile traffic violations in terms of forensics. linguistic perspective. This study uses a descriptive qualitative approach. Data collection techniques are recording, recording, and interviewing. The results of this study indicate that teenagers who violate traffic regulations tend to cover up their mistakes by providing convoluted information or information. This can be seen from the answers given to the police. During the interrogation process, many violations of Grice's cooperative principle. In addition, the police need to pay attention to the language patterns used when interrogating youths who violate traffic rules so that the juveniles can provide information about the violations committed without pressure and coercion.